2013
DOI: 10.1016/j.jss.2012.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Gαq G proteins modulate MMP-9 gelatinase during remodeling of the murine femoral artery

Abstract: Background Vessels heal after injury and G protein-coupled receptors are involved in the vascular smooth muscle cell (VSMC) proliferation required to form intimal hyperplasia. We have previously identified the role of Gαq in VSMC proliferation in vitro. This study now examines the role of Gαq in the developing intimal hyperplasia in a murine model and the impact of disruption of Gαq signaling on intimal hyperplasia development. Methods The murine femoral wire injury model was employed in which a micro wire i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Sham operated vessels did not produce such a response (18, 19). Cell apoptosis peaked within 3 days and cell proliferation peaked at 7 days after injury.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sham operated vessels did not produce such a response (18, 19). Cell apoptosis peaked within 3 days and cell proliferation peaked at 7 days after injury.…”
Section: Discussionmentioning
confidence: 92%
“…We had previously demonstrated that under normal circumstances, murine injured femoral arteries developed intimal hyperplasia, which is maximal at 28 days and does not change substantially between day 28 and day 56 (18, 19). Sham operated vessels did not produce such a response (18, 19).…”
Section: Discussionmentioning
confidence: 99%